Global and gene‐specific DNA methylation across multiple tissues in early infancy: implications for children's health research. Issue 5 (29th January 2014) - Armstrong, David A.; Lesseur, Corina; Conradt, Elisabeth; Lester, Barry M.; Marsit, Carmen J.
ABSTRACT: An increasing number of population studies are assessing epigenetic variation in relation to early‐life outcomes in tissues accessible to epidemiologic researchers. Epigenetic mechanisms are highly tissue specific, however, and it is unclear whether the variation observed in one of the tissue types is representative of other sources or whether the variation in DNA methylation is distinct, reflecting potential functional differences across tissues. To assess relations between DNA methylation in various samples from newborns and children in early infancy, we measured promoter or gene‐body DNA methylation in matched term placenta, cord blood, and 3–6 mo saliva samples from 27 unrelated infants enrolled in the Rhode Island Child Health Study. We investigated 7 gene loci ( KLF15, NR3C1, LEP, DEPTOR, DDIT4, HSD11B2, and CEBPB ) and global methylation, using repetitive region LINE‐1 and ALUYb8 sequences. We observed a great degree of interlocus, intertissue, and interindividual epigenetic variation in most of the analyzed loci. In correlation analyses, only cord blood NR3C1 promoter methylation correlated negatively with methylation in saliva. We conclude that placenta, cord blood, and saliva cannot be used as a substitute for one another to evaluate DNA methylation at these loci during infancy. Each tissue has a unique epigenetic signature that likely reflects their differential functions. Future studies should consider the uniqueness of these features, to improve epigenetic biomarker discovery and translation.—Armstrong, D. A., Lesseur, C., Conradt, E., Lester, B. M., Marsit, C. J. Global and gene‐specific DNA methylation across multiple tissues in early infancy: implications for children's health research. FASEB J . 28, 2088–2097 (2014). www.fasebj.org